INTEGRATING THERAPEUTIC ARCHITECTURE AND OCCUPATIONAL THERAPY IN DRUG REHABILITATION DESIGN: A SPATIAL AND OCCUPATIONAL FRAMEWORK FOR RECOVERY AND REINTEGRATION - Alya Tanaya Riznita; Wahyu Abdillah (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The increasing prevalence of substance use disorders (SUD) in Indonesia is not matched by adequate rehabilitation facilities, highlighting the need for more effective and holistic approaches. This study proposes an integrated design strategy for a drug rehabilitation center by combining therapeutic architecture with occupational therapy (OT) to support recovery and social reintegration. Using a qualitative design-based research approach, the study translates behavioral characteristics of users and rehabilitation processes into spatial and architectural strategies. Therapeutic architecture principles such as natural lighting, ventilation, and connection to nature are applied to enhance emotional stability and reduce stress [11][2]. Occupational therapy is implemented through structured activity-based programming to rebuild daily routines and meaningful occupations [1][9]. A key contribution of this study is the integration of hospitality-based programs and mangrove-based activities as forms of real-world occupational engagement. These programs enable users to develop vocational skills, social interaction, and adaptive behaviors within a controlled yet realistic environment. The findings demonstrate that architecture can function as an active therapeutic system when integrated with occupation-based programming, facilitating behavioral transformation, reducing relapse risk, and supporting long-term recovery through the integration of spatial design, meaningful activity, and environmental context.